The structural regulation of H-bonding network in the chemically-bonded polyimide/silica nanocomposite with excellent mechanical stability and improved moisture resistance - Hao Wang; Ziqiao Wang; Naihang Kuang; Yujiu Yang; Chunhua Zhang (Materials & Design)
Polymer-based nanocomposites, being widely concerned for lightweight and high-strength functional materials, still exhibit irreversible failures to resist mechanical damage and water erosion. In this paper, a kind of hydroxyl-rich silica nanomaterial was prepared and used for fabricating the chemically-bonded polyimide (PI)/hydroxyl-rich silica (SiO2-OH) nanocomposite through the surface-initiated curing and the coupling reaction, which then regulate the H-bonding network within the PI matrix. As a result, the prepared nanocomposite performed excellent thermal stability (Tg reaches 442.5℃) and improved mechanical properties. The improved nano-construction incorporates the film with the rebuilt H-bonding network to improve the moisture resistance of the PI matrix. This work, focusing on the constitution of chemically-bonded silicon-containing nanocomposite structure, will promote an in-depth understanding of the relationship between structure and properties of polymer film materials, being beneficial for the development of modern polymer-based materials of long-term service life.